The Hand of Stalin: Leningrad - Walker, John (United Kingdom : October Films ; PTV Productions, 1990)
The film looks at the effects on Leningrad of "the Great Terror" which swept the Soviet Union in the late 1930s, when spies and "enemies of the state" were seen everywhere. Through the stories of five survivors from Leningrad and some of the informers and Secret Police, the darkness and paranoia of the time are revealed and the spiraling effect demands on informers.
Keywords: Documentary films